Climate change and economic activity: evidence from US states. (11th November 2022) - Mohaddes, Kamiar; Ng, Ryan N. C.; Pesaran, M. Hashem; Raissi, Mehdi; Yang, Jui-Chung
Abstract: We investigate the long-term macroeconomic effects of climate change across 48 US states over the period 1963–2016 using a novel econometric strategy that links deviations of temperature and precipitation (weather) from their long-term moving-average historical norms (climate) to various state-specific economic performance indicators at the aggregate and sectoral levels. We show that climate change has a long-lasting adverse impact on real output in various states and economic sectors, and on labour productivity and employment in the United States. Moreover, in contrast to most cross-country results, our within US estimates tend to be asymmetrical with respect to deviations of climate variables (including precipitation) from their historical norms.